Morphofunctional characteristics of young elite male handball players - Ilic, V.; Macura, M. (Archivos de medicina del deporte, 2008)
Specific morphology and functional characteristics of athletes are very important prerequisite for successful sport pursuiting. The aim of this study was to examine middle values of anthropometric and functional parameters in our young elite male handball players and to analyze their specificities i.e. the probable variation between the four playing positions (goalkeepers, back court players, wings, pivots). Method: The sample in the present study comprised 32 elite male handball players age 19,3 (±1,3) years, and with sport probation 8,3 (±1,9) years. Body composition (BMI, percentage of body fat (%D), muscle (%M) and bone (%O)) was calculated by measuring body weight, body height, 6 skinfold thicknesses, 4 limb circumference, and 4 joint diameter. Vo2max was estimated by Astrand`s test on ergobicycle. Results: Average value of BMI was 24,32kg/m 2 , percentage of body fat (%D=13,79%), muscle (%M=50,32%), bone (%O=16,72), and VO2max was 3,40l/min (39,67ml/kgmin). Goalkeepers were found to be the tallest players, and they had the largest fat skinfolds and the highest fat percentage, but their aerobic capacity was the lowest. The players on wing positions had the highest percentage of body muscles, and pivots had the best aerobic capacity. Conclusion: We may conclude that anthropometric and functional differences exist among handball players who play in different positions. These differences fit with their different workload in a game. Therefore, training programs should include specific sessions for each positional role